Peranan Manajemen Sumber Daya Manusia dalam Organisasi - Disa Halsa; Hawignyo Hawignyo; Didit Supriyadi (Universitas Batanghari, 2022)
Human resource management is a process to solve every problem to support existing activities in an organization or company. Organizations and companies can survive the threats of change and time. This study explains that the role of Human Resource Management (HR) in an organization or company is to achieve organizational or business goals in an effective and efficient manner. Writing aims to determine the role of human resource management in the organization. The writing method uses the literature review method (library research). From the discussion it can be concluded that human resource management is managing human resources. Of all the resources in the organization, human resources are very important and very decisive. All the potential of human resources is very influential on the organization's efforts to achieve goals.